Hospital Dentistry: the importance of the Dentist Surgeon in the prevention of oral infections in the Intensive Care Unit (ICU): a literature review (Research, Society and Development, 2022)
In the hospital environment, the dental surgeon acquires new functions, his role with the multidisciplinary team is to ensure the patient's comfort and avoid the worsening of his clinical conditions. In the ICU, the patient is exposed to numerous infections due to his fragile condition. Therefore, inadequate hygiene can cause serious systemic diseases, caused by microorganisms present in the oral microbiota. Thus, the objective of the present study was to identify the main oral diseases found in ICU patients and the influence on the emergence of systemic infections, as well as to show which are the most common systemic diseases observed in these patients and their relationship with the oral cavity. For this, a bibliographic review of the literature was carried out, through the search for articles that presented a relevant topic for this review in the Scientific Electronic Library Online (ScieELO), Virtual Health Library (BVS) and PubMed databases, between the years of 2012 to 2022. It is concluded, therefore, that the presence of the Dental Surgeon in the multidisciplinary team is necessary, since this professional has knowledge and management of the appropriate techniques for the elaboration of adequate protocols of oral hygiene, contributing to the elimination of infectious foci in the oral cavity, as well as curative treatment. In this way, he works to improve the patient's systemic condition, favoring his quality of life.